2018
DOI: 10.1111/jep.12913
|View full text |Cite
|
Sign up to set email alerts
|

Translational validity of PASAT and the effect of fatigue and mood in patients with relapsing remitting MS: A functional MRI study

Abstract: Our results show that poorer performance on the PASAT is associated with higher activation in areas connected with working memory, attention, and emotional processes during the fMRI assessment with PVSAT paradigm, which provides evidence for the translational validity of the PASAT in patients with RRMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…During the “repeat” condition, the participants were instructed to silently repeat once each presented number. There were four blocks of each type, alternating between add and repeat followed always by a 21 s “off” block representing a centrally located fixation cross, during which the participants were instructed to look at the cross without thinking of anything in particular (12).…”
Section: Methodsmentioning
confidence: 99%
“…During the “repeat” condition, the participants were instructed to silently repeat once each presented number. There were four blocks of each type, alternating between add and repeat followed always by a 21 s “off” block representing a centrally located fixation cross, during which the participants were instructed to look at the cross without thinking of anything in particular (12).…”
Section: Methodsmentioning
confidence: 99%
“…Functionally, resting-state functional MRI (rs-fMRI) has attracted increasing attention to be used to explore intrinsic brain activity and connectivity (Fox and Greicius, 2010; Iancheva et al, 2018; Kandilarova et al, 2018; Zhao et al, 2018). Several studies of MSA-p type found the disruption of the striatal-thalamo-cortical (STC) network, default mode network (DMN), visual associated cortices (Wang et al, 2017), as well as cerebello-thalamo-cortical (CTC) network (Yao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroscience operates validation procedures on an essentially similar basis, in search for post hoc correlations with the associated psychological scores and several papers in this Special Section exemplify an attempt to methodologically integrate the data from neuroscience with those from clinical psychological and neuropsychiatric evaluation. Here, the works by Kandilarova and colleagues, Haralanov, Terziivanova, and associates, Iancheva and co‐workers, and Gaberova, Yordanova, and colleagues are noteworthy and should be read alongside the contribution by Matanova et al who discuss the importance of brain‐based therapeutic strategies, although the identification of various inconsistencies calls for further investigations within the frameworks outlined.…”
Section: Translating the Findings Of Neuroscience Into Clinical Medicmentioning
confidence: 99%